Chinese culture and its impact on China's development - Sun, Dongyun; Sun, Guodong 1979- (World Scientific, 2022)
"This book analyzes the importance of culture and the impact of culture on China's development. It studies strategic and cutting-edge theoretical topics on civilization revival, cultural development and cultural (re)construction in the Chinese context. Topics covered in the book include the position of Chinese culture in the history of world civilizations, the cultural revival in contemporary China, the function of Confucian culture in modern society, the rightful rule of the construction of Chinese cultural identity in transitional China, the pluralistic symbiosis of contemporary Chinese cultures, reconstruction of national ideology, the development of the cultural soft power and the cultural industry in contemporary China, the establishment of China's international image, among others"